PERILAKU WAKIF DALAM MEWAKAFKAN TANAHNYA UNTUK KESEJAHTERAAN MASYARAKAT - AHMAD MUZAYYAN HAQQY; H. BUSAINI; IHSAN ROIS (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2017)
The theme of the article is "economy based on the principles of Islam". Wakaf is one of the instruments in the Islamic economy for the welfare of the community. In this study, explained that people in the district of Kediri, West Lombok regency have a high motivation to give donation of land although many people are under the poverty line. This happens because wakif in the district of Kediri understood as charity wakaf for the provision of the reward in the Hereafter will continue to flow because it is used to build educational facilities and mosques as a means of worship for the wider community. Utilization of wakaf for public welfare in the district of Kediri aims to 1. Eliminating ignorance and educate the people by building educational facilities, 2. Reduce Poverty and open up employment opportunities, 3. Eliminating social inequalities with the participation of most of the people managing the wakaf.